Diagnosis and treatment outcomes of primary lymphoma of the thyroid gland - Omar Hamdy; Gehad A. Saleh; Ramadan Ayman Selim; Radwa M. Abdelsattar; Maryam M. Dawood; Youssef Y. Abbas; Rana Abdo; Yousef M. Mansour; Jana M. AbuZahra; Mohamed Elsayed; Ahmed E. Eladl; Shaimaa El-Ashwah; et al. (Discover Oncology)
Abstract Introduction Primary thyroid lymphoma (PTL) is a rare extranodal malignancy accounting for less than 5% of thyroid cancer, with a unique algorithm of management in contrast to other types of thyroid cancer, where surgery is the cornerstone of management. PTL usually shows female predominance, and diffuse large B-cell lymphoma (DLBCL) is the most prevalent pathological subtype. In this study, we aimed to assess thyroid lymphoma’s epidemiology, patterns of relapse, diagnostic approaches, and prognostic features, presenting a 16.5-year experience at a tertiary referral oncology center. Methods This retrospective study assessed PTL patients managed between January 2008 and June 2024 at a tertiary referral center. All the clinical, diagnostic, therapeutic, and follow-up data were analyzed. Results Sixteen patients were included, with a mean age of 59.34 years and a female-to-male ratio of 1.7. Most cases (68.8%) were diagnosed at stage II, with DLBCL identified in 93.8% of patients. Remission was achieved in half of the patients after first-line therapy, with no cures following second-line treatments. All the patients who died were stage II at the time of diagnosis. The median disease-free survival (DFS) was 35 months, and the overall survival (OS) was 37.5 months. Conclusion Being aware of PTL can facilitate the timely initiation of treatment. Chemotherapy is the definitive treatment, used alone or with surgery, if done for diagnostic purposes. PTL has a good prognosis, however, late-stage disease can be linked to worse outcomes. This study underscores the importance of multimodal diagnostic and therapeutic strategies while highlighting the need for further research into this rare malignancy.